Determinants of continued usage intention of electronic human resource management - Yusliza, Mohd-Yusoff; Yi Yong, Jing; Ramayah, T; Imran Tanveer, M.; Muhammad, Zikri (International Journal of Engineering and Technology, 2018)
This study examines on a model extension of the attitude towards using Electronic Human Resource Management (E-HRM) by linking attitude to E-HRM continuance usage intention. Technology Continuance Theory (TCT) is adapted and integrated with Technology Acceptance Model (TAM), Expectation Confirmation Model (ECM), and Cognitive Model (COG) and empirical findings from prior studies about continued use of information systems. Research hypotheses derived from this model are empirically validated using the responses to a survey on E-HRM usage, collected from 193 E-HRM users. Based on the valid response collected from a survey questionnaire, Partial Least Square (PLS) was employed to examine the research model. The results indicated that the perceived usefulness, attitude and satisfaction were positively related to continuance usage intention of E-HRM. Perceived ease of use, satisfaction and perceived usefulness were positively related to attitude. Perceived usefulness and confirmation were also found to be positively related to satisfaction. Perceived ease of use and confirmation were found to be positively related to perceived usefulness. Future empirical studies based on the model studied in this paper should help identify areas with significant impact on usersâ€™ continuance usage intention towards using E-HRM technology in a fast-moving environment. This study is a pioneer study of continuance usage intention with E-HRM, especially of the relationship between continuance usage intention and its determinants.Â Â